The type specimens of Atelopus moreirae Miranda-Ribeiro, 1920 , with notes on the taxonomic status of Atelopus moreirae massarti Cochran, 1948 (Amphibia, Anura, Bufonidae) - Caramaschi, Ulisses; Jr., José P. Pombal (Zootaxa, 2025)
Atelopus moreirae [currently Melanophryniscus moreirae (Miranda-Ribeiro, 1920)] was described on basis of an undefined number of specimens collected in the “Itatiaya”. The type series has not been designated in the original description, and the type locality of the species was referred only in a vague manner. In this paper we revise the specimens examined by Miranda-Ribeiro and define the type series of A. moreirae. In order to better define the type series of the species, a lectotype is designated and the paralectotypes are defined; the type locality is defined and georeferenced. The known distribution of the species is mapped. Additionally, the taxonomic status of Atelopus moreirae massarti Cochran, 1948 is analysed and its synonymy under Melanophryniscus moreirae (Miranda-Ribeiro, 1920) is confirmed, resulting in the conclusion that it should not be considered a valid species or subspecies.